Tasks of social marketing in connection with the complex sustainability challenges - Klausmann-Dinya, Anikó; Dinya, László (Journal of Central European Green Innovation, 2021)
The most recent global climate summit (COP26) in Glasgow recently concluded. There is a broad consensus that important agreements have been reached in the right direction, but implementation is still far from being achieved. Within the framework of our current socio-economic operation (paradigm), resolving the climate crisis and sustainability seem unfeasible. The experience of our previous projects aimed at sustainable regional development also clearly shows that no radical steps can be expected from above (decision-makers in a privileged position). (Dinya - Dinya, 2020) This requires much stronger social pressure from below, which cannot be achieved without extremely intensive and professional social marketing (fact-based awareness of trends, threats and actions). This is why we have been dealing with the growing importance of the role of social marketing for years. (Dinya – Dinya, 2019) We believe that the solution to the extremely complex challenges of sustainability is also greatly hindered by the fact that society (globally, nationally and locally) is highly manipulated: the fact-based approach (common sense; that is, the prevalence of ‘natural intelligence’) is overshadowed by the mass of misleading false news (the strengthening of ‘artificial unintelligence’ in our own name). While this thesis applies to all of our complex societal challenges, the Covid epidemic as well as migration, this time we want to outline a diagnosis and what to do about it in terms of sustainability. This was based on a special processing of the Eurobarometer database. (Eurobarometer, 2021)